Correlation Between Baseline 18F-FDG PET/CT Findings and CD38- and CD138-Expressing Myeloma Cells in Bone Marrow and Clinical Parameters in Patients with Multiple Myeloma - Arzu Cengiz; Hayri Üstün Arda; Firuzan Döğer; İrfan Yavaşoğlu; Yakup Yürekli; Ali Zahit Bolaman (Turkish Journal of Hematology, 2018)
Objective: The aim of this study was to evaluate the relation between the rate of fluorine-18 (18F) fludeoxyglucose (FDG) uptake and CD38 and CD138 expression in myeloma cells in bone marrow and other clinical parameters in patients with multiple myeloma (MM). Materials and Methods: Patients with the diagnosis of MM who underwent 18F-FDG positron emission tomography/computed tomography (PET/CT) for initial staging were evaluated retrospectively. We analyzed a total of 42 patients (43-83 years old, mean: 64.4+-9.9). Hematological and biochemical tests including hemoglobin, hematocrit, C-reactive protein, β2-microglobulin, creatinine, albumin, calcium, lactate dehydrogenase, and erythrocyte sedimentation rate were recorded. In bone marrow samples, plasma cell ratio and CD38 and CD138 immunohistochemical staining were evaluated. On PET/ CT images, mean standardized uptake values (SUVmean) of the right anterior and posterior iliac crest and right proximal femora were calculated. The correlations between the average SUVmean of bone marrow and CD38- and CD138-expressing myeloma cells and other parameters were analyzed by Spearman's correlation test. Values of p<0.05 were considered statistically significant. Results: Types of MM were IgGK (45%), IgGL (21%), IgAK (7%), IgAL (10%), and others (17%). Thirty-two (76%) patients were at stage III according to the Salmon-Durie staging system. There was a statistically significant positive correlation between bone marrow FDG uptake and percentage of plasma cells in bone marrow and CD38 and CD138 expression in plasma cells (r=0.403, r=0.339, and r=0.409) and β2-microglobulin and C-reactive protein levels (r=0.676, r=0.541). There was a negative correlation between bone marrow FDG uptake and hemoglobin and hematocrit values (r=-0.377 and r=-0.368). Other hematological parameters were not correlated with FDG uptake in bone marrow. Conclusion: Increased FDG uptake is correlated with the percentage of CD38 and CD138 expression in plasma cells in bone marrow. In addition to initial staging, 18F-FDG PET/CT is useful in treatment planning and prognostic evaluation in MM patients.